Novel Probiotic Strain Lactiplantibacillus plantarum CNTA 628 Modulates Lipid Metabolism and Improves Healthspan in C. elegans - Ignacio Goyache; Lorena Valdés-Varela; Raquel Virto; Miguel López-Yoldi; Noelia López-Giral; Ana Sánchez-Vicente; Fermín I. Milagro; Paula Aranaz (Applied Sciences, 2025)
The call for new approaches to prevent and treat metabolic syndrome-related diseases has led to research on the use of lacto-fermentative probiotics with beneficial metabolic properties like Lactobacilli. Here, we characterize the probiotic properties of a novel strain, Lactiplantibacillus plantarum CNTA 628, and investigate its potential anti-obesity and health-promoting activities in the Caenorhabditis elegans model, additionally elucidating the molecular mechanisms involved. Lactiplantibacillus plantarum CNTA 628 exhibited sensitivity to the entire spectrum of antibiotics analyzed, gastric and intestinal resistance in vitro, β-galactosidase and bile-salt hydrolysate activities, and the capacity to form biofilms and produce SCFAs. In addition, it reduced the binding of the pathogenic E. coli O157:H7 to intestinal epithelial cells (Caco-2) and exerted immune-modulating effects in cellular models. Supplementation with this probiotic significantly reduced C. elegans fat accumulation by more than 18% under control and high-glucose conditions, lowered senescence, improved oxidative stress, and significantly enhanced lifespan without affecting the development of the worms. Gene expression analyses evidenced that L. plantarum CNTA 628 plays a role in regulating daf-22 and maoc-1 gene expression, both linked to beta-oxidation pathways. Our results demonstrate the health-benefiting properties of this novel strain and suggest its potential as probiotic candidate for the prevention and treatment of metabolic syndrome-related conditions.